54 Effect of Direct Fed Microbials on Apparent Nutrient Digestibility and the Fecal Microbial Population in the Sedentary Horse. (10th April 2018) - Phillips, C A; Cavinder, C A; Rude, B J; Memili, E; Smith, T
Abstract: Probiotic supplementation in the diets of horses has yielded mixed results, with some studies proposing an increase in nutrient digestibility through alteration of the hindgut microbiota. The ability for equine producers to improve forage digestibility, for instance, may offer a way to enhance diets without compromising gastrointestinal health. Hay quality can be variable; therefore, optimizing nutrient digestibility of various quality forages through probiotics deserves further study. Six stock-type horses (8 ± 3.2 yr; 494.68 ± 53.470 kg) were used in a 4 x 4 Latin square study lasting 168 d to determine the effect of direct fed microbials (DFM) on apparent nutrient digestibility and the fecal microbial population. Horses were fed 0.5% BW/d of control (CON) grain or grain with DFM added and 1% BW/d of low quality (LQ) bermudagrass hay or high quality (HQ) alfalfa hay. The DFM contained Lactobacillus acidophilus, Lactobacillus casei, Bifidobacterium thermophilum, Enterococcus faecium, and Saccharomyces cervisiae at a rate of 25.1 x 10 9 cfu/g of grain, averaging 62.1 x 10 12 cfu/d. After a 21 d washout period, horses were gradually transitioned to 1 of 4 diets for a 21 d treatment period. Fresh per rectum fecal samples were collected in a staggered manner (n = 4/d) during the last 2 d of each washout and treatment period. Samples were plated and the top 3 isolates were phenotypically identified and sensitivities determined. During the last 72 h of each treatment period, a total fecal collection was performed utilizing modified fecal collection bags. Feces were collected at 0100, 0700, 1300, and 1900 and weighed, homogenized, and a 5% representative sample taken. Statistical analysis was performed using the MIXED procedure of SAS with horse within diet as a random block effect. Apparent crude protein digestibility tended (P < 0.065) to be greater in HQ + DFM than in HQ + CON. Apparent NDF, ADF, EE, and nonstructural carbohydrate digestibilities indicated no differences (P > 0.05) within hay quality regardless of treatment. Period was significant for apparent digestibilities of DM (P = 0.048) and hemicellulose (P = 0.044). Period by diet was significant for apparent digestibilities of OM (P = 0.035) and ash (P = 0.023). Observational assessments in fecal bacteria from washout to treatment period found that DFM seemed to repress potentially pathogenic bacteria excretion in LQ but not in HQ. Results indicate DFM may have an impact on nutrient digestibility and microbial populations dependent on diet. The concentration of DFM supplemented yielded no negative physiological results.